Substitute? Or not?

Algebra Level 4

Let a , b , c a, b, c be rational numbers such that c = a b a + b c=-\frac { ab }{ a+b } . Which of the following expressions is correct?

This problem is part of the set Hard Equations

( a + b + 2 c ) 2 = a 2 + b 2 4 c 2 { (a+b+2c) }^{ 2 }={ a }^{ 2 }+{ b }^{ 2 }-4{ c }^{ 2 } ( a + b + c ) 3 = a 3 + b 3 + c 3 { (a+b+c) }^{ 3 }={ a }^{ 3 }+{ b }^{ 3 }+{ c }^{ 3 } ( a + b + c ) 2 = a 2 + b 2 + c 2 { (a+b+c) }^{ 2 }={ a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 } ( a + b + c ) ( a 2 + b 2 + c 2 ) = a 3 + b 3 + c 3 + a b c (a+b+c)({ a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 })={ a }^{ 3 }+{ b }^{ 3 }+{ c }^{ 3 }+abc a + b + c = a 3 + b 3 + c 3 a+b+c={ a }^{ 3 }+{ b }^{ 3 }+{ c }^{ 3 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Anandhu Raj
Feb 2, 2015

Given c = a b a + b c=-\frac { ab }{ a+b }

We could rewrite as c ( a + b ) = a b c(a+b)=-ab

c a + c b = a b \Longrightarrow ca+cb=-ab

a b + b c + a c = 0 \Longrightarrow ab+bc+ac=0 ------------------(1)

Also we know that ( a + b + c ) 2 = a 2 + b 2 + c 2 + 2 ( a b + b c + a c ) { (a+b+c) }^{ 2 }={ a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }+2(ab+bc+ac)

Using ( 1 ) (1) ,

( a + b + c ) 2 = a 2 + b 2 + c 2 \boxed{{ (a+b+c) }^{ 2 }={ a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }}

good solution

Sai Ram - 5 years, 10 months ago

Log in to reply

Thank you :)

Anandhu Raj - 5 years, 10 months ago

Log in to reply

I up voted it

Sai Ram - 5 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...